PENGARUH KEPERCAYAAN DAN KOMITMEN SERTA BAURAN PEMASARAN JASA TERHADAP LOYALITAS KONSUMEN DI HOTEL ZAKIAH MEDAN - Nurul Widyawati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
The objective of this study is to investigate the simultaneous and partial effect of trust, commitment,  and marketing mix on customer loyalty at Zakiah Hotel Medan.The sample of this study are 150 customers at  Zakiah Hotel Medan. This study uses  probability sampling by simple random sampling. And data are estimated by using multiple linear regression model.The empirical result of this study with F-test shows that trust, commitment, and marketing mix influence customer loyalty at Zakiah Hotel Medan. The result with partial t-tes shows that trust (X1) by t-tes (3,8463) >t-tab(1,9764), commitment (X2) by t-test (4,4248) > t-tab(1,9764;) and marketing mix (X3) by t-test (7,0702) > t-tab (1,9764) influence to customer loyalty at Zakiah Hotel Medan.